Sexo não é brincadeira: o sentido de infância para adolescentes inseridas na exploração sexual comercial - Farias, Deliane Macedo de (2008)
The childhood has being highlighted by the great concern about the several contexts in which children are inserted, amongst them, commercial sexual exploitation (CSE). The experience of this violence process brings implications to the person constitution. Thus, this research aimed to understand how commercial sexual exploited adolescents to signify the childhood. Participated of this research four female adolescents that had been assisted by Programa de enfrentamento ao Abuso e Exploração Sexual de Crianças e Adolescentes (Sentinela) , with ages between 12 and 17 years. The corpus was composed by the combination of the semi-structured interview and other procedures, like childish stories, draws and photography. Moreover, we used another instruments to constitute the corpus, like the documental research and we proposed the construction of a life story book of each participant. The corpus was analyzed through the Thematic Content Analysis. Five thematic axes emerged from the participants discourse and theoretical perspective: dynamical of family, scholar process, ludic behavior, conception of childhood and insertion on CSE process. The participants presented a conception about childhood as been a preparation and education phase to ingress in adult life. In other words, while children do not grown up, they go to the school, plays, lives with family, are happy and do not have any responsibilities. Nevertheless, the life experience of these girls was implicated by negligence, sexual abuse, child labor, institutionalization and, evidently, the commercial sexual exploitation. Understanding that the childhood experienced by adolescent, as well as, her insertion on CSECA, constitutes her, while person, we investigated how the interrelation expresses it on participants future perspectives. Their goals are defined based on family constitution and professional improvement, although feelings of disillusion and pessimism had been showed up in some moments. According these results, we pointed to the necessity of the effective proposals that promote real improvement of adolescents life quality, through, in which they could to create alternatives to get over the several risks in which they are exposed, mainly, the CSECA condition